Building Character Through Community: The Transformative Power of Social Activity-Based Education - Mariyani Mariyani; Dadang Sundawa (LP. Ma'arif Janggan Magetan, 2025)
This study aims to explore the effectiveness of social activity-based character education through a case study of involvement in the Rumah Belajar Ceria. The research approach used is qualitative with a case study design. Data collection techniques include interviews with three informants selected using a purposive sampling technique, as well as activity observations and documentation. The data analysis technique used in this study follows the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. Data analysis was carried out comprehensively and traingulation was carried out. The results of the study show that social activities in society significantly support character formation. This effectiveness is achieved when individuals meet several aspects, including an understanding of character values, active involvement in social activities, and tangible behavioral transformations. Community plays an important role in creating a collective learning environment that encourages character development such as empathy, responsibility, and cooperation. Intense communication and interaction in society serve as external factors that reinforce the internalization of these values. This research underscores the importance of social activities in character education, not only as a means of individual learning but also as a mechanism to strengthen social relationships in society.